IMPLIKASI TANGGUNG JAWAB TERHADAP KEPUASAN KERJA YANG DIMEDIASI ASPIRASI KARIR PADA PEGAWAI DINAS PENDIDIKAN PROVINSI ACEH - Maya Fela Yati; Hamdi Harmen (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to measure the effect of responsibility on job satisfaction with career aspirations as a mediating variable for employees of the Aceh Provincial Education Office. The population in this study were all employees of the Aceh Provincial Education Office, which amounted to 242 people. The sampling technique in this study was carried out by probability samplingwhere the whole population will be used as samples. Data collection equipment used in this study is a questionnaire. The analysis technique used in this study is SimpleRandomSampling.Based on the results of the study, indicating that responsibility has a positive effect on work satisfaction, responsibility has a positive effect on career aspirations, career aspirations have a positive effect on job satisfaction, and responsibility influences employee job satisfaction at the Aceh Provincial Education Agency through career aspirations.